Effect of seed bed types on growth and yield of onion seedlings (Allium cepa L.) Under the influence of fertilizer types in Makurdi, Nigeria - Ifeoma, Odiaka, Ngozi; Kemi, Akinyemi Bosede; Detuhan, Ugese Felix; Richard, Ugoo Tavershima; Mercy, Injor Madoo; Moses, Nyam Tyokyaa (International Journal of Sustainable Agricultural Research, 2024)
Field experiments was conducted at the Teaching and Research Farm, Joseph Sarwuan Tarka University Makurdi to evaluate the effect of bed types and fertilizer types on the growth and yield of onion seedlings/bulbs (Allium cepa L.). The study was a 2x4 factorial experiment {2 types (bed and ridge) and four fertilizer types (NPK20:10:10, poultry manure, cattle dung, and no application served as control)} laid out in a Randomized Complete Block Design (RCBD) replicated thrice. Data were collected were subjected to Analysis of Variance (ANOVA) and Fisher's least significant difference (FLSD) was used to separate means. Results of the study revealed that onions raised on beds had statistically higher growth and yield parameters than the ridge bed system. Therefore, the onion planted on bed type system recorded the highest yields with bulb weight (13.45t/ha) and (23.35 t/ha) in both years. On the fertilizer types, NPK 20:10:10 application recorded the highest bulb weight of 14.57t/ha and 35.75t/ha in both years, followed by poultry manure with bulb weight of 11.29t/ha and 11.61t/ha and cattle dung with bulb weight of 10.70t/ha and 12.94t/ha while untreated (control) gave the lowest yields with bulb weight/plot 9.21t/ha and 7.40t/ha respectively. It is recommended that the application of NPK 20:10:10 fertilizers on bed type system be adopted for optimum yield of Onions in Makurdi, Nigeria. Furthermore, in the scarcity or high cost of NPK fertilizers, smallholder farmers in the study location can adopt either poultry manure or cattle dung as a substitute to boost yields of onions.